Effect of In3+ doping on electroluminescence from MgZnO:In3+/ZnO:Er3+/n-Si LEDs. (9th May 2017) - Huang, Miaoling; Wang, Shenwei; Yin, Xue; Mu, Guangyao; Wan, Guangmiao; Duan, Xiaoxia; Yi, Lixin
Abstract: Rare earth (RE)-related electroluminescence (EL) devices have a wide range of applications in full-color display due to its spectrally pure emissions and insensitivity to the surrounding environment. Here we report a set of MgZnO:In 3+ /ZnO:Er 3+ /n-Si light-emitting diodes with different In concentrations prepared by a radio frequency magnetron sputtering method. The current–voltage characteristics and EL spectra are presented. With an increase in the In dopant concentration, the forward threshold voltage of the devices drops significantly. Moreover, we find that EL intensity can be tuned effectively at the same time, and the highest luminous efficiency can be achieved at an appropriate In concentration. These results suggest that an In-doping method can improve performance effectively in RE-related light-emitting devices for full-color display.